Collaborative work in the 6th & 8th grade orchestra class: to develop student leaders - Fischer, Zachery John (My University, 2025)
In this report, I describe how students in 6th-8th grade collaborated on the following areas of growth and development: always keeping consistent steady beat when counting correct rhythms in one's part, watching as well as listening to the director's and ensemble's set tempo, and working together as a team. In my career as a music educator, I have often witnessed students taking the lead during warm-ups or specific concert excerpts they were preparing. During those moments, I realized how impactful and effective those rehearsals were and how engaged everyone was from start to end. To accomplish this project, I used what I learned in my master’s courses focusing on Violin/Viola and Cello/String Bass pedagogy to develop ways my students could create and design lessons on their own to collaborate with their peers. Instead of my former role as a teacher who controlled everything that was being taught and learned, I now get the chance to help and guide my students in how to create, perform, and respond to each other as the observer and facilitator in the classroom. I can see how my students lead, teach, and motivate each other to work as a team, while I follow. My master's degree broadened my understanding of my teaching strategies and improved my teaching methods. This degree also identified and created my own ideas of my personal music philosophy. Everyone deserves the opportunity to gain experience and experience music education. This experience in music education should always apply to one's life in and outside of the classroom. Humans do not gain a music education without putting in hard work and effort every day. This idea led me to the creativity I put into these lessons. My goal was for my students to teach and learn from one another at the highest success level possible.
Keywords: Collaborative; Work; Orchestra; Develop; Student; Leaders